A just transition for US workers is within reach. (4th March 2021) - Walsh, Jason
ABSTRACT: We must respond to the climate crisis on the scale science demands. At the same time, working people should not suffer economically due to efforts to tackle climate change. Increasing unionization and improving job-quality in clean energy industries – including offshore wind generation and manufacturing sectors such as the electric vehicle industry – can drive climate action and ensure a just transition for workers.